O ensino da matemática por meio da resolução de problemas: um estudo das questões da OBMEP sobre perímetro e área - Modolo, Talita Moraes (2023)
Geometry plays a fundamental role in our daily lives, manifesting itself in various forms and contexts. For this reason, its teaching becomes extremely important. Considering the issues faced in the teaching and learning of Plane Geometry in basic education, the present research aims to create a bank of questions aimed at Mathematics teachers to assist them in using the OBMEP test perimeter and area questions in the classroom, based on the questions from the second phase of Level 1 of OBMEP. The data collection was carried out through documentary research, exploring the problems presented in the editions of the exam held between 2005 and 2022. Throughout the research, the questions and their respective official solutions will be presented, along with a proposed resolution, to exemplify and guide the application of the problem-solving practice proposed by Polya for the teaching of area and perimeter. In addition to providing support to teachers, it is expected that the discussions carried out in this paper will also contribute to a reflection on the teaching of Mathematics in public schools in the country, seeking improvements in the teaching and learning process for those who are part of these institutions.